Assessment of High School Students’ Learning and Development of Qualities and Competencies: A Case Study - Hung, Tran Van; Tuan, Dang Ngoc; Thanh, Ngo Tu (Journal of Education and e-Learning Research, 2022)
This study aims to assess high school students' learning outcomes, their achievement of goals and fulfilling academic requirements and how the entire teaching and learning process takes place. The study, consisting of an experimental group and a control group was conducted for pre-test and post-test comparisons of the academic performance of 88 10th grade students. 44 students were selected as the experimental group that underwent a specific teaching strategy to monitor their development of qualities and competencies in one semester, and the remaining 44 students acted as the control group. The data collected after the tests were analyzed using SPSS software (V20). The results showed that the students in the experimental group had better academic results than those in the control group. The findings of this study have implications for policy, further research as well as approaches for the assessment of students’ development of qualities and competencies in Vietnam.